Glucosinolate diversity in seven field-collected Brassicaceae species - Lisa Pormetter; Marina Pfalz; Mervic D. Kagho; Philipp Klahn; Heiko Vogel; Juergen Kroymann; Ute Wittstock (PLoS ONE, 2025)
The glucosinolate-myrosinase system is a well-known chemical defense in the Brassicales order, which has been extensively studied in Arabidopsis thaliana . Here, we assessed natural variation of leaf glucosinolate content and profiles in seven species of the Brassicaceae family, using over 300 cauline leaf samples collected from wild populations in Germany and France. Total glucosinolate content varied substantially among individuals, populations and species. Analysis of glucosinolate profiles identified two types of profiles each for Cardamine amara and C. pratensis , and three profile types for C. impatiens . One profile type for each Cardamine species showed glucosinolate compositions distinct from previously described profile types. In contrast, the glucosinolate profiles of the other four species – Lepidium draba , Lunaria rediviva , Hesperis matronalis , and Descurainia sophia – were less variable. The obtained dataset paves the way for more detailed analyses of the genetic basis of glucosinolate biosynthesis in these species. Our data indicate that, among plutellid species whose larvae feed exclusively on cruciferous host plants, the oligophagous Eidophasia messingiella and Rhigognostis senilella are exposed to a diverse array of glucosinolate structures. In contrast, Plutella porrectella primarily encounters only a limited set of unusual glucosinolates when feeding on its preferred host plant, H. matronalis . Future research is required to evaluate whether this has led to specialized adaptations in this Lepidopteran herbivore. Furthermore, our study indicates that the unpredictable variation in total glucosinolate content as detected in our field-collected samples might pose a substantial challenge even to adapted herbivores.